Anti-Biofilm and Anti-Inflammatory Properties of the Truncated Analogs of the Scorpion Venom-Derived Peptide IsCT against Pseudomonas aeruginosa - Pornpimon Jantaruk; Kittitat Teerapo; Supattra Charoenwutthikun; Sittiruk Roytrakul; Duangkamol Kunthalert (MDPI AG, 2024)
Pseudomonas aeruginosa is an opportunistic pathogen in humans and a frequent cause of severe nosocomial infections and fatal infections in immunocompromised individuals. Its ability to form biofilms has been the main driving force behind its resistance to almost all conventional antibiotics, thereby limiting treatment efficacy. In an effort to discover novel therapeutic agents to fight P. aeruginosa-associated biofilm infections, the truncated analogs of scorpion venom-derived peptide IsCT were synthesized and their anti-biofilm properties were examined. Among the investigated peptides, the IsCT-Δ6-8 peptide evidently showed the most potential anti-P. aeruginosa biofilm activity and the effect was not due to bacterial growth inhibition. The IsCT-Δ6-8 peptide also exhibited inhibitory activity against the production of pyocyanin, an important virulence factor of P. aeruginosa. Furthermore, the IsCT-Δ6-8 peptide significantly suppressed the production of inflammatory mediators nitric oxide and interleukin-6 in P. aeruginosa LPS-induced macrophages. Due to its low cytotoxicity to mammalian cells, the IsCT-Δ6-8 peptide emerges as a promising candidate with significant anti-biofilm and anti-inflammatory properties. These findings highlight its potential application in treating P. aeruginosa-related biofilm infections.